2020
DOI: 10.3389/fendo.2020.00207
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Multimodal Therapy for Anaplastic Thyroid Carcinoma: 125I Seed Implantation Plus Apatinib After Surgery

Abstract: Anaplastic thyroid cancer is known to be the most lethal malignancy among endocrine tumors for its extremely limited survival rate after diagnosis. As a result of this poor survival prognosis, multimodal therapy is currently under investigation to address this global concern. In this reported case, the 125 I seed implantation and vascular endothelial growth factor receptor-2 (VEGFR-2) inhibitor apatinib were co-applied to treat a 49-year-old woman with anaplastic thyroid cancer. After the patient began apatini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…There are case reports, describing the pre- (30) and postoperative (31) use of the selective VEGFR-2/SRC inhibitor apatinib in single patients, but no clinical studies have thus far been published.…”
Section: Resultsmentioning
confidence: 99%
“…There are case reports, describing the pre- (30) and postoperative (31) use of the selective VEGFR-2/SRC inhibitor apatinib in single patients, but no clinical studies have thus far been published.…”
Section: Resultsmentioning
confidence: 99%
“…[ 32 , 33 ] Of note, previous studies from our hospital also found that apatinib had better efficacy, a more manageable safety profile and faster therapeutic responses. [ 9 , 34 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical trials have revealed its hopeful anticancer effect in various solid tumors, [ 7 , 8 ] and a similar result in TC was found in our team's previous research. [9] Herein, we report a case of a locally advanced inoperable DTC patient who underwent complete safe removal after undergoing preoperative short term apatinib targeted treatment, with little drug-related side effects and almost no postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
“…This scheme can be proven to be a feasible alternative treatment for ATC patients who cannot undergo surgery. 42 …”
Section: I Seed Implantation Combined With Molecular Targeted Drugsmentioning
confidence: 99%